This Is So NP! - Elizaveta Bylinina (Baltic International Yearbook of Cognition, Logic and Communication, 2010)
The construction we are discussing is a recent American English construction (though it can be found in a number of other languages as well) with an individual-denoting noun phrase (NP) in the predicate position modified by a degree modifier that typically occurs with gradable adjectives, as in 'This is so Obama!' We attempt to look deeper into the structure and compositional semantics of this construction, and though we do not provide a complete analysis of it, we believe that the study of this construction can contribute to questions of gradable predicate semantics, multidimensionality, degree constructions and proper name semantics.